Assessing Fisheries Activities at the Modern Fish Market in Muara Baru, North Jakarta - Yuli Andriani; Renita Aulia; Rusky I. Pratama (International Journal of Scientific Multidisciplinary Research, 2023)
The Muara Baru Modern Fish Market, situated at Muara Baru Street No. 27 in North Jakarta, Indonesia serves as a contemporary hub for fish trade. This study aims to outline fishing activities and discern activity patterns between sellers and consumers within the market. Employing a qualitative descriptive method, this research leverages observation and literature study data collection techniques. The findings underscore the Muara Baru Modern Fish Market as a dynamic space for regular interactions between sellers and consumers, featuring distinctive activity patterns. Consumers engage in various activities, including dining at the food court and sourcing culinary ingredients. Interestingly, this pattern persists beyond specific hours, extending from the afternoon well into the midnight hours. The bargaining process and interactive exchanges between traders and consumers emerge as pivotal elements shaping the market's dynamics. This established routine not only ensures consumer comfort but also guarantees the sustained vitality of trade within the Muara Baru Modern Fish Market